"Women Photographers in the 80s": Narratives About an Exhibition Dedicated to Women - Nichele, Heloisa; Corrêa, Ronaldo de Oliveira (ARS, 2023)
In this article, we propose a reconstruction of the exhibition “Mulheres fotógrafas anos 80”, promoted by Funarte's National Institute of Photography in 1989, in Rio de Janeiro. From a documentary investigation based on fragmentary and heterogeneous records, such as reports, newspaper notes, and the resulting catalog of the exhibition, we were able to create preliminary narratives about the production, circulation and reception of the exhibition that coincide with social agendas and collective policies, such as feminist movements, the process of institutionalization of photography in Brazil, and the adhesion of women to the professional field. Finally, we intend to contribute to the visibility of events disregarded by historiography, in order to expand the versions about the participation of women in the history of Brazilian photography.